Can Foreign Exchange Intervention Stem Exchange Rate Pressures from Global Capital Flow Shocks? - Blanchard, Olivier (IMF Working Papers; Working Paper ;, 2015)
Many emerging market economies have relied on foreign exchange intervention (FXI) in response to gross capital inflows. In this paper, we study whether FXI has been an effective tool to dampen the effects of these inflows on the exchange rate. To deal with endogeneity issues, we look at the response of different countries to plausibly exogenous gross inflows, and explore the cross country variation of FXI and exchange rate responses. Consistent with the portfolio balance channel, we find that larger FXI leads to less exchange rate appreciation in response to gross inflows.